2000
DOI: 10.1139/w00-042
|View full text |Cite
|
Sign up to set email alerts
|

Amylase hyper-producing haploid recombinant strains ofThermomyces lanuginosusobtained by intraspecific protoplast fusion

Abstract: Amylase hyper-producing, catabolite-repression-resistant, recombinant strains were produced by intraspecific protoplast fusion of thermophilic fungus Thermomyces lanuginosus strains, using well-characterized, morphological, and 2-deoxy-D-glucose resistant markers. The fusant heterokaryons exhibited enhanced amylase activities as compared to the amylase hyper-producing parental strain (T2). Diploids derived from heterokaryons segregated to stable haploid recombinant strains. In the haploid strain (Tlh 4q), appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These were in good agreement with other studies. 22,39,40 The colonies germinating from YJ9 protoplasts were then screened by clamp connection observation and DCPI staining to identify monokaryons. 25 Approximately 83 colonies were screened and only 14 were shown to be monokaryotic.…”
Section: Resultsmentioning
confidence: 99%
“…These were in good agreement with other studies. 22,39,40 The colonies germinating from YJ9 protoplasts were then screened by clamp connection observation and DCPI staining to identify monokaryons. 25 Approximately 83 colonies were screened and only 14 were shown to be monokaryotic.…”
Section: Resultsmentioning
confidence: 99%
“…The strain A. fumigatus TF3 was able to grow optimally at 50ºC and also produced maximum amount of pectinase at 50ºC. Thermophilic fungi have been reported to optimally produce enzymes at 50ºC (22,23). Loudiere et al, (15) reported higher temperatures for optimum activity, 50-60ºC for only 20% activity was quantified.…”
Section: Discussionmentioning
confidence: 99%
“…Using semi-quantitative plate assay approach, a thermophilic fungal strain TF3 (Aspergillus fumigatus MTCC 4163) isolated from decomposing orange peel waste, was selected as the best producer of pectinase and PG. The plate assay approach has been previously employed in our lab for isolating hyper amylase producing mutants/fusants of thermophilic fungus Thermomyces lanuginosus (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These evaluations were performed twice. Complementation was evaluated by a dual culture technique on MM plates, and it was ascertained if an aerial mycelium was formed at the contact zone between two distinct nit mutants [16][17][18].…”
Section: A New Methods For Producing Hybrid Strains Of the Entomopathomentioning
confidence: 99%